2011
DOI: 10.1016/j.polymer.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and gelation characteristics of photo-crosslinkable star Poly(ethylene oxide-co-lactide-glycolide acrylate) macromonomers

Abstract: Viability of encapsulated cells in situ crosslinkable macromonomers depends strongly on the minimum concentration of polymerization initiators and monomers required for gelation. Novel 4-arm poly(ethylene oxide-co-lactide-glycolide acrylate) (SPELGA) macromonomers were synthesized and characterized with respect to gelation, sol fraction, degradation, and swelling in aqueous solution. SPELGA macromonomers were crosslinked in the absence of N-vinyl-2-pyrrolidone (NVP) monomer to produce a hydrogel network with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 41 publications
(56 reference statements)
1
40
1
Order By: Relevance
“…23,25 Briefly, the residual moisture was removed from the PEG macromer by azeotropic distillation from toluene. The PEG macromer and lactide monomers were heated to 120°C under dry nitrogen atmosphere in a reaction flask equipped with an overhead stirrer.…”
Section: Synthesis Of Lactide-capped Peg Macromermentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 Briefly, the residual moisture was removed from the PEG macromer by azeotropic distillation from toluene. The PEG macromer and lactide monomers were heated to 120°C under dry nitrogen atmosphere in a reaction flask equipped with an overhead stirrer.…”
Section: Synthesis Of Lactide-capped Peg Macromermentioning
confidence: 99%
“…Hydrophobicity of the peptide was varied by capping PEG chain ends with 0-6 lactide monomers. PEG as an inert matrix with tunable properties [22][23][24] was used for encapsulation of hMSCs to isolate and investigate the effect of BMP-2 peptide hydrophobicity on its osteoinductive potential. Experimental and simulation results revealed that osteoinductive potential of the BMP-2 peptide is correlated with its CMC and the concentration of free peptide in aqueous medium and not the total peptide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Based on NMR results, the average degree of acrylation was 89% and there was on average 1.8 -0.1 acrylates in the PEGDA macromer. Disk-shaped hydrogels with 8-mm diameter and 750-mm thickness were fabricated for determination of elastic modulus and cell encapsulation.…”
Section: Macromer Characterization and Hydrogel Modulusmentioning
confidence: 99%
“…The gelation kinetics of physical micellar gels depends on the strength and number density of physical crosslinks [105,107]. The gelation kinetics of covalently-bonded chemical gels depends on several factors including the concentration and distribution of crosslinkable groups and initiator [104,[108][109][110]. Figure 3a shows the gelation time of photocrosslinkable star poly(ethylene glycol-co-lactide) acrylate (SPELA) macromers with respect to concentration of UV photo-initiator.…”
Section: Gelation Timementioning
confidence: 99%
“…Copolymerization of PEG with a degradable polymer like poly(lactide) (PLA) has been used to impart degradability to PEG hydrogels. The degradation and water content of the copolymers can be adjusted by the fraction of hydrophobic lactide segments [131,132] but solubility of the copolymer in aqueous solution was adversely affected by increasing the lactide content [133]. In addition, other hydrolytically degradable polymers including polyphosphoesters [134,135], poly(ester amides) [136] and poly(amino-ester urethanes) [137] have been used to synthesize degradable hydrogels.…”
Section: Degradationmentioning
confidence: 99%